Short communication: Effect of mycoviruses on growth, spore germination and pathogenicity of the fungus Fusarium circinatum - Juan Asdrúbal Flores-Pacheco; Emigdio Jordán Muñoz-Adalia; Pablo Martínez-Álvarez; Valentín Pando; Julio J. Díez-Casero; Jorge Martín-García (Forest Systems, 2018)
Aim of the study: To assess the impact on two mycoviruses recently described in F. circinatum mitovirus 1, and 2-2 (FcMV1 and FcMV2-2) on i) mycelial growth, ii) spore germination and iii) relative necrosis.